Optimum initial masking level for Plateau seeking method - Rahmat, Sarah; Jamaluddin, Saiful Adli (2010)
The purpose of this study is to establish the optimum initial masking level that can be used in “Plateau Method” of masking. The Minimum Effective Masking Level (MEML) of 30 normal hearing ears was determined at octave frequencies from 250Hz to 4000Hz. Mean MEML for the octave frequencies ranged from -1.8 to 0.7 dB SL. There were significant differences of MEML between 250 Hz and 2 KHz, and 250 Hz and 4 KHz (P <0.05) with higher MEML recorded at higher frequencies as compared to 250Hz. MANOVA revealed no significant difference of MEML between male and female across frequencies (P<0.05). Pearson correlation revealed a strong positive significant linear relationship between pure tone level and masker level for all frequencies (P<0.05; 0.95<r<1.0) which suggests that the narrowband noise used effectively masked the pure tone signals. The highest recorded MEML was 5 dB SL at all octave frequencies. Taking a conservative approach, this value was used in the calculation of optimum initial masking level in addition to 5 dB to ensure significant threshold shift. It is recommended that 10 dB SL of initial masking level is applied in audiology clinics in Malaysia as it is adequate to effectively mask the pure tone thresholds.